Implementasi E-Procurement Ditinjau Dari Kesuksesan Sistem Teknologi Informasi Dengan Menggunakan Model Delone dan Mclean - Yunus Harjito; Fatchan Achyani; Payamta Payamta (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
This study aims to obtain empirical evidence on the success of e-procurement implementation by the local government, viewed from system and information quality. The implementation success refers to the use and users satisfaction, which contribute to organizations and individuals inside. The research method is quantitative method using questionnaire. The research population is procurement committee in local government, while the sample are the procurement committee members in Surakarta City Government. The data were analyzed using SmartPLS ver.2.0.M3. The results of the statistical analysis show that the system quality does not influence the user satisfaction and use. The information quality has a positive influence to the user satisfaction and actual use. While actual use does not influence the user satisfaction. Moreover, user satisfaction and use also gives a positive influence to the individual impact and the individual impact gives positive impact to the organizational impact.